Small biomolecule sensors based on an innovative MoS2–rGO heterostructure modified electrode platform: a binder-free approach. Issue 45 (8th November 2017) - Saraf, Mohit; Natarajan, Kaushik; Saini, Anoop Kumar; Mobin, Shaikh M.
Abstract : Hydrothermally synthesized MoS2 –rGO nanoflowers can simultaneously sense ascorbic acid (AA), dopamine (DA) and uric acid (UA) with good separating peak-to-peak potentials. Abstract : The requirement of sensitive diagnostic chips for small biomolecules has triggered the urgent development of versatile nanomaterial based platforms. Therefore, numerous materials have been designed with fascinating properties. Herein, we report a facile one-pot synthesis of MoS2 –rGO nanoflowers grown by the hydrothermal method and their applicability in the simultaneous sensing of AA, DA and UA. The structure and morphology of nanoflowers have been probed by various physico-chemical techniques such as XRD, SEM/TEM, AFM, Raman and XPS. Furthermore, these nanoflowers were used to construct a glassy carbon based working electrode (MoS 2 –rGO/GCE ), by a facile drop-casting method in the absence of any commercial binder. The electrochemical investigations revealed high separating potency of theMoS 2 –rGO/GCE towards AA, DA and UA with distinguishable oxidation potentials (AA–DA = 204 mV and DA–UA = 122 mV) and a notable detection limit and reasonable sensitivity for each of these biomolecules. The charge transfer resistance and capacitive components obtained by electrochemical impedance spectroscopy (EIS) were found to be in agreement with the voltammetric observations. The observed synergy between MoS2 and rGO opens up new possibilities to consider the MoS2 –rGO nanostructures as the cutting edge material for electrochemical sensor development.